Insurance market penetration and economic growth in Eurozone countries: Time series evidence on causality - Saurav Dash; Rudra Prakash Pradhan; Rana Pratap Maradana; Kunal Gaurav; Danish B. Zaki; Manju Jayakumar (Future Business Journal, 2018)
This paper examines the causal relationship between insurance market penetration and per capita economic growth in 19 Eurozone countries for the period 1980-2014. We use three different indicators of insurance market penetration (IMP), namely life insurance penetration, non-life insurance penetration, and total (both life and non-life) insurance penetration. We particularly emphasize on whether Granger causality exists between these variables both ways, one way, or not at all. Our empirical results perceive both unidirectional and bidirectional causality between IMP and per capita economic growth. However, these results are mostly non-uniform across the Eurozone countries during this selected period. The policy implication is that the economic policies should recognize the differences in the insurance market and per capita economic growth in order to maintain sustainable growth in the Eurozone.
Keywords: L96; O32; O33; O43; 650; Eurozone countries; Granger causality; IMP; Per capita economic growth